(untitled) (Global Journal of Human-Social Science, 2022)
This paper aims to present and analyze an episode regarding the application of a didactic activity in the written modality on the study of the Portuguese Language related to Alphabetical Order withdrawn from a Portuguese Language TB 3 adapted to Libras 4 The participants in this investigation are deaf fifth-grader elementary school students in a special and bilingual school public system in the state of Minas Gerais Brazil The respondents answers reveal that the intention to promote a second language learning environment led by a pedagogical activity that has not been experienced in their first language makes it unfeasible to access and reflect on L2 5 The sign language adaptation of the didactic activity did not help the understanding of the exercise proposal as in the Portuguese language In summary it is evinced that didactic materials with proposals for adaptation and accessibility in SL 6 for deaf students are inadequate and do not build learning in L2